Young Children Detect and Avoid Logically Inconsistent Sources: The Importance of Communicative Context and Executive Function. Issue 6 (18th June 2016) - Doebel, Sabine; Rowell, Shaina F.; Koenig, Melissa A.
Abstract : The reported research tested the hypothesis that young children detect logical inconsistency in communicative contexts that support the evaluation of speakers' epistemic reliability. In two experiments ( N = 194), 3‐ to 5‐year‐olds were presented with two speakers who expressed logically consistent or inconsistent claims. Three‐year‐olds failed to detect inconsistencies (Experiment 1), 4‐year‐olds detected inconsistencies when expressed by human speakers but not when read from books, and 5‐year‐olds detected inconsistencies in both contexts (Experiment 2). In both experiments, children demonstrated skepticism toward testimony from previously inconsistent sources. Executive function and working memory each predicted inconsistency detection. These findings indicate logical inconsistency understanding emerges in early childhood, is supported by social and domain general cognitive skills, and plays a role in adaptive learning from testimony.